Analisis Karakter Jujur pada Film Animasi Hafiz dan Hafizah - Dianti Yunia Sari; Ulpah, Fauziah (UIR PRESS, 2023)
Honest character is one of the characters that needs to be introduced to children from an early age. Honest character can accustom children to act as they are and not lie. To instill the character value of honesty in early childhood can be through a good example or model. The model itself can be a film or an individual who can provide a positive example for children. The animated film Hafiz and Hafizah is one of the films that presents positive content about good behavior for early. Such honest behavior. So indirectly children can get to know honest characters through an animated film. The purpose of this research is to describe and find out the results of honest character analysis in the animated film Hafiz and Hafizah. This study uses a qualitative approach, with qualitative descriptive research methods through content analysis techniques for the animated films Hafiz and Hafizah by observing and recording through showing episodes from 2020 to 2022. There are five episodes from the animated films Hafiz and Hafizah, namely 1) trusting a wallet, 2) greed becomes a problem, 3) Hafiz's smart pen is missing, 4) the bazzar for goodness, and 5) an Islamic children's song, let's tell the truth. The results of research on honest character analysis in the animated film Hafiz and Hafizah contain honest characters that are suitable for early childhood such as be and tell the truth, admit mistakes and apologize for mistakes that have been made.